Optimalisasi Peran Organisasi Kemahasiswaan dalam Mewujudkan Mahasiswa FTIK UIN K.H. Abdurrahman Wahid Pekalongan yang Unggul dan Moderat di Era Society 5.0 - Akhmad Dalil Rohman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the role of student organizations in the Faculty of Tarbiyah and Teaching Science (FTIK) UIN K.H. Abdurrahman Wahid Pekalongan in forming superior and moderate students. The main problem studied is the role of student organizations in student development and what impact this has on understanding the values ​​of moderation and religious diversity. The research method used is in-depth interviews with students, student organization officials, and related administrative staff. The research results show that student organizations play an important role in developing leadership, empowerment and community service skills for FTIK students. In addition, this organization also plays a role in promoting understanding of the values ​​of moderation and religious diversity, which are becoming increasingly relevant in the context of the geotechnological Society 5.0 Era.